Nutrientes no solo e na solução do solo na citricultura fertirrigada por gotejamento - Souza, Thais R. de; Bardiviesso, Diógenes M.; Andrade, Thomas F. de [UNESP]; Villas Bôas, Roberto L. [UNESP] (Associação Brasileira de Engenharia Agrícola, 2015)
Soil solution analysis has shown to be a promising method for soil fertility diagnosis, mainly in fertigation systems. The objective of this study was to evaluate the behavior of nutrients in soil and soil solution by supplying five doses of N, P2O5 and K2O (0, 25, 50, 100 and 200% of the recommended dose) via fertigation. The experiment was conducted during three seasons in Valencia sweet orange on Swingle rootstock. Soil and soil solution samples were collected after fertigation at each season. The supplied doses of N, P2O5 and K2O decreased pH in both soil and soil solution; however soil solution variation was 3.5 times higher. Such differences were also observed for P and K contents, which were 65 times and above 100 times higher than in soil, respectively. These nutrients had similar behavior in both environments with correlation values of 0.87 and 0.97 respectively, and both values of P and K increased according to fertilizer dose. The results suggested that soil solution analysis can be used as a tool to estimate values of pH, P, K, Mn and Zn in the soil, as well as to determine nitrogen availability in citrus production under fertigation systems.

A análise da solução do solo vem mostrando-se um método promissor de diagnóstico da fertilidade de solo, principalmente em sistemas de fertirrigação. O objetivo deste estudo foi avaliar o comportamento dos nutrientes no solo e na solução do solo, quando fornecidas cinco doses de N, P2O5 e K2O (0; 25; 50; 100 e 200% da dose recomendada) via fertirrigação. O experimento foi conduzido por três safras em laranjeiras Valência enxertadas sobre citrumelo Swingle. O solo e a solução do solo foram coletados ao final do período de fertirrigação de cada safra. As doses de N, P2O5 e K2O aplicadas proporcionaram redução nos valores de pH do solo e da solução do solo, porém a variação dos valores de pH da solução do solo foi 3,5 vezes maior que a observada no solo. Para o P, esta variação ficou em torno de 65 vezes e, para o K, foi maior que 100 vezes. Os teores de P e K apresentaram comportamento semelhante no solo e na solução do solo, com valores de correlação de 0,87 e 0,97, respectivamente, e ambos os teores de P e K aumentaram em função das doses de fertilizantes. Os resultados sugerem que a análise da solução do solo pode ser utilizada como ferramenta para estimar os valores de pH, P, K, Mn e Zn no solo, e também para determinar a disponibilidade de nitrogênio em sistemas de fertirrigação na citricultura.
Soil and soil solution nutrient content in drip fertigated citrus
Keywords: Citrus sinensis; Soil solution extractor; Soil fertility; extrator de solução do solo; fertilidade do solo